PENGARUH STRUKTUR MODAL, PERENCANAAN PAJAK DAN KEBIJAKAN DIVIDEN TERHADAP PROFITABILITAS (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR KESEHATAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023) - Mirra Sri Wahyuni; Irzan Irzan; Furqonti Ranidiah; Rina Yuniarti (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to analyze the influence of capital structure, tax planning, and dividend policy on profitability in healthcare companies listed on the Indonesia Stock Exchange for the 2019–2023 period. The research method employed is quantitative, utilizing secondary data obtained from company financial reports on the official Indonesia Stock Exchange website (www.idx.co.id). Data analysis techniques included descriptive statistics and multiple linear regression analysis using SPSS version 26. The research sample was determined using a purposive sampling method, resulting in 45 observational samples from nine healthcare companies. The results indicate that partially, capital structure has a negative and significant effect on profitability, dividend policy has a positive and significant effect on profitability, while tax planning has no effect on profitability. Simultaneously, capital structure, tax planning, and dividend policy have a significant effect on profitability. The conclusion of this study is that capital structure management and dividend policy play a significant role in increasing the profitability of healthcare companies, while tax planning has not been shown to have a significant effect on corporate profitability. Keywords: Capital Structure, Tax Planning, Dividend Policy, Profitability, Healthcare Sector